2019
DOI: 10.1002/ecs2.2667
|View full text |Cite
|
Sign up to set email alerts
|

Ecological mechanisms can modify radiation effects in a key forest mammal of Chernobyl

Abstract: Nuclear accidents underpin the need to quantify the ecological mechanisms which determine injury to ecosystems from chronic low‐dose radiation. Here, we tested the hypothesis that ecological mechanisms interact with ionizing radiation to affect natural populations in unexpected ways. We used large‐scale replicated experiments and food manipulations in wild populations of the rodent, Myodes glareolus, inhabiting the region near the site of the Chernobyl disaster of 1986. We show linear decreases in breeding suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Conversely, others report significant impacts of radiation on wildlife at extremely low dose rates. For instance, significant reductions in invertebrate numbers over dose rates which are in the typical range for natural background exposures (Møller and Mousseau, 2009), LD50 values (the lethal dose required to kill 50% of exposed individuals) for butterfly larvae (Hiyama et al, 2012) below the commonly used generic 'predicted no effect dose rate' of 10 µGy h -1 (Andersson et al, 2009; see discussion in Copplestone and Beresford, 2014) and 'significant radiation effects' on bank vole populations at ambient dose rates of 1 µSv h -1 or less (Mappes et al, 2019). If such studies have been correctly conducted and interpreted, then the results would have implications for the system of radiation protection for both the environment and humans (Beresford and Copplestone, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, others report significant impacts of radiation on wildlife at extremely low dose rates. For instance, significant reductions in invertebrate numbers over dose rates which are in the typical range for natural background exposures (Møller and Mousseau, 2009), LD50 values (the lethal dose required to kill 50% of exposed individuals) for butterfly larvae (Hiyama et al, 2012) below the commonly used generic 'predicted no effect dose rate' of 10 µGy h -1 (Andersson et al, 2009; see discussion in Copplestone and Beresford, 2014) and 'significant radiation effects' on bank vole populations at ambient dose rates of 1 µSv h -1 or less (Mappes et al, 2019). If such studies have been correctly conducted and interpreted, then the results would have implications for the system of radiation protection for both the environment and humans (Beresford and Copplestone, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…rivers). As previous research has found no effect of environmental radiation on ground level plant coverage (0-50 cm), the most important vegetation variable for bank voles (Mappes et al 2019), no large differences in food sources among our trapping locations were not expected. We used Ugglan Special2 live traps (Grahnab, Sweden) baited with potato and sunflower seeds and distance between neighboring trapping sites was at least 1 km.…”
Section: Study Animalsmentioning
confidence: 42%
“…Reproductive costs in females could explain the smaller organ size, since bank vole females can have up to ten pups in one litter (Koskela et al 1998). A link between radiation and reproductive output was shown in a previous study where ambient radiation level was negatively correlated with female litter size (Lehmann et al 2016;Mappes et al 2019).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations